Locus coeruleus noradrenergic neurons and CO2 drive to breathing - Biancardi, Vivian [UNESP]; Bicego, Kenia C. [UNESP]; Almeida, Maria Camila [UNESP]; Gargaglioni, Luciane H. [UNESP] (Springer, 2008)
The Locus coeruleus (LC) has been suggested as a CO2 chemoreceptor site in mammals. In the present study, we assessed the role of LC noradrenergic neurons in the cardiorespiratory and thermal responses to hypercapnia. To selectively destroy LC noradrenergic neurons, we administered 6-hydroxydopamine (6-OHDA) bilaterally into the LC of male Wistar rats. Control animals had vehicle (ascorbic acid) injected (sham group) into the LC. Pulmonary ventilation (plethysmograph), mean arterial pressure (MAP), heart rate (HR), and body core temperature (T-c, data loggers) were measured followed by 60 min of hypercapnic exposure (7% CO2 in air). To verify the correct placement and effectiveness of the chemical lesions, tyrosine hydroxylase immunoreactivity was performed. Hypercapnia caused an increase in pulmonary ventilation in all groups, which resulted from increases in respiratory frequency and tidal volume (V-T) in sham-operated and 6-OHDA-lesioned groups. The hypercapnic ventilatory response was significantly decreased in 6-OHDA-lesioned rats compared with sham group. This difference was due to a decreased V-T in 6-OHDA rats. LC chemical lesion or hypercapnia did not affect MAP, HR, and T-c. Thus, we conclude that LC noradrenergic neurons modulate hypercapnic ventilatory response but play no role in cardiovascular and thermal regulation under resting conditions.
Keywords: Chemosensitivity; A6; Hypercapnia; Ventilation; Pons; catecholamine